The effects of stress biomarkers on sex hormones, sperm quality and quantity in infertile men in Abuja, Nigeria - S. P., Abriba; H. B., Osadolor (International Journal of Research in Medical Sciences, 2023)
Background: Studies have shown the adverse effects of stress on infertility. It has been reported that 40% of infertility cases are attributed to the men. Therefore, this study is aimed at determining the effects of stress biomarkers on sex hormones, sperm quality, and quantity in men investigating infertility. Method: A total of one hundred and fifty-two (152) participants were recruited into a case control study between September 2018 to August 2019. Prolactin, testosterone, follicle stimulating hormone (FSH), luteinizing hormone (LH), salivary cortisol and salivary alpha amylase were estimated using both competitive and non-competitive enzyme linked immunosorbent assay (ELISA) techniques; semen was examined directly after liquefaction according to world health organization criteria. Results: The mean and standard deviation of testosterone, FSH, sperm cells count and sperm activity (%) were significantly lower (p<0.05) in the men study group relative to the control group; while prolactin, salivary cortisol and alpha amylase were significantly higher (p<0.05) in the men study group relative to the control group. There was no significant difference in the value of LH in the men study group compared with the men control group (p>0.05). Conclusions: Stress in men affects sex hormones, semen quality and quantity. Both conditions of oligospermia and azospermia were observed in the men study group, with associated hormonal abnormalities, decrease in sperm quality, quantity and elevated stress biomarkers.